Aspects of Pentecostal Christianity in Zimbabwe (Springer International Publishing, 2018)
This edited book offers an engaging portrait into a vital, religious movement inside this southern Africa country. It tells the story of a community of faith that is often overlooked in the region. The authors include leading scholars of religion, theology, and politics from Botswana and Zimbabwe. The insights they present will help readers understand the place of Pentecostal Christianity in this land of many religions. The chapters detail a history of the movement from its inception to the present. Chapters focus on specific Pentecostal churches, general doctrine of the movement, and the movement's contribution to the country. The writing is deeply informed and features deep historical, theological, and sociological analysis throughout. Readers will also learn about the socio-political and economic relevance of the faith in Zimbabwe as well as the theoretical and methodological implications raised by the Pentecostalisation of society. The volume will serve as a resource book both for teaching and for those doing research on various aspects of the Zimbabwean society past, present, and future. It will be a good resource for those in schools and university and college departments of religious studies, theology, history, politics, sociology, social anthropology, and related studies. Over and above academic and research readers, the book will also be very useful to government policy makers, non-governmental organizations, and civic societies who have the Church as an important stakeholder.